1984
DOI: 10.1159/000115700
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Study of the Sural Nerve in Fabry’s Disease

Abstract: A man with Fabry’s disease, who died at 52, suffered from lancinating limb pains between the age of 20 and 27, and from severe arthralgia between 20 and 40. The sural nerve showed a severe loss of fibers (1,614 myelinated fibers/mm2), chiefly affecting the small myelinated fibers. Inclusions of both homogeneous and lamellated appearance were present in the perineurial cells, fibroblasts and vessel walls. Teased fibers displayed moderate remyelination, regeneration and the presence of globular focal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0
2

Year Published

1985
1985
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 0 publications
1
27
0
2
Order By: Relevance
“…The progression of the neuropathy seemed extremely slow, since only occasional fibres were degenerating. There were a few clusters of regenerating fibres in patient 1, as reported in [7], but not in patient 2. Teased fibre study showed that 5% of the isolated fibres were remyelinated and the rest were normal in patient 1, with no significant changes in patient 2.…”
mentioning
confidence: 64%
See 3 more Smart Citations
“…The progression of the neuropathy seemed extremely slow, since only occasional fibres were degenerating. There were a few clusters of regenerating fibres in patient 1, as reported in [7], but not in patient 2. Teased fibre study showed that 5% of the isolated fibres were remyelinated and the rest were normal in patient 1, with no significant changes in patient 2.…”
mentioning
confidence: 64%
“…Teased fibre study showed that 5% of the isolated fibres were remyelinated and the rest were normal in patient 1, with no significant changes in patient 2. Some cases showing mild or moderate de-remyelintaed fibres, 12.3% of the isolated fibres in [7] and 4.3% in [15] have been reported in the teased fibre studies. Figure 4 shows the MF histogram.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Symptoms include episodes of extremity pain or acroparesthesia, gastrointestinal symptoms, hypohidrosis and associated heat sensitivity (Cable et al, 1982;Ries et al, 2005;Rowe et al, 1974) (Table 1). Pain has been linked with small fiber neuropathy (Attal & Bouhassira, 1999) and is thought t o b e c a u s e d b y e i t h e r r e d u c e d p e r f u s i o n o f p e r i p h e r a l n e r v e s o r g l y c o s p h i n g o l i p i d accumulation in neural or perineural cells (Gadoth & Sandbank, 1983;Gemignani et al, 1984). Pain has been described as burning and starts in the hands and feet but can radiate proximally.…”
Section: Early Clinical Featuresmentioning
confidence: 99%